Counterintuitive Chemistry: Carbene Stabilization of Zero-Oxidation State Main Group Species - Wang, Yuzhong; Robinson, Gregory H. (Journal of the American Chemical Society, 2023)
Carbenes have evolved from transient laboratory curiosities to a robust, diverse, and surprisingly impactful ligand class. A variety of different carbenes have significantly contributed to the development of low-oxidation state main group chemistry. This Perspective focuses upon advances in the chemistry of carbene complexes containing main group element cores in the formal oxidation state of zero, including their diverse synthetic strategies, unusual bonding and structural motifs, and utility in transition metal coordination chemistry and activation of small molecules.